Eye tracking for spatial research: Cognition, computation, challenges. Issue 1 (2nd January 2017) - Kiefer, Peter; Giannopoulos, Ioannis; Raubal, Martin; Duchowski, Andrew
Abstract : Spatial information acquisition happens in large part through the visual sense. Studying visual attention and its connection to cognitive processes has been the interest of many research efforts in spatial cognition over the years. Recent technological developments have led to an increasing popularity of eye-tracking methodology for investigating research questions related to spatial cognition, geographic information science (GIScience) and cartography. At the same time, eye trackers can nowadays be used as an input device for (cognitively engineered) user interfaces to geographic information. We provide an overview of the most recent literature advancing and utilizing eye-tracking methodology in these fields, introduce the research articles in this Special Issue, and discuss challenges and opportunities for future research.